Comparison of the Kinetic Parameters of Alternative Oxidases From Trypanosoma brucei and Arabidopsis thaliana—A Tale of Two Cavities - Xu, Fei; Copsey, Alice C.; Young, Luke; Barsottini, Mario R. O.; Albury, Mary S.; Moore, Anthony L. (Frontiers in Plant Science, 2021)
The alternative oxidase (AOX) is widespread in plants, fungi and some protozoa. While the general structure of the AOX remains consistent, the overall activity varies between species, as well as sources of kinetic activation and their sensitivity to inhibitors. In this study, the recombinant rTAO (Trypanosoma brucei AOX) and rAtAOX1A (Arabidopsis thaliana AOX1A) were expressed in the E. coli ∆hemA mutant FN102 and the kinetic parameters of purified AOXs were compared. Results showed that rTAO possessed the highest Vmax and Km for quinol-1, whilst much lower Vmax and Km were observed in the rAtAOX1A. The catalytic efficiency (kcat/Km) of rTAO was higher than that of rAtAOX1A. The rTAO also displayed the higher oxygen affinity compared to rAtAOX1A. It should be noted that rAtAOX1a was sensitive to α-keto acids while rTAO was not. Nevertheless, only pyruvate and glyoxylate can fully activate Arabidopsis AOX. In addition, rTAO and rAtAOX1A showed different sensitivity to AOX inhibitors; ascofuranone (AF) being the best inhibitor against rTAO, whilst colletochlorin B (CB) appears to be the most effective inhibitor against rAtAOX1A. Octylgallate (OG) and salicylhydroxamic acid (SHAM) are less effective than the other inhibitors against protist and plant AOX. Caver analysis indicated that the rTAO and rAtAOX1A differ with respect to the mixture of polar residues lining the hydrophobic cavity which may account for the observed difference in kinetic and inhibitor sensitivities. The data obtained in this study is not only beneficial for our understanding of the variation in kinetics of AOX within protozoa and plants, but also contributes to the guidance for the future development of phytopathogenic fungicides.